2017
DOI: 10.5539/jas.v9n11p30
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Parasites of Red Lionfish, Pterois volitans from the Veracruz Coral Reef System, Mexico, Southern Gulf of Mexico

Abstract: A helminthological survey was conducted on 78 red lionfish, Pterois volitans, collected in the Veracruz Reef System National Park (VRSNP). Register: trematodes (5 spp.), cestodes (1), and nematodes (2). Prevalence per species < 30% and mean intensity < 6.0. Three new host records are reported herein. The red lionfish is infected by species of endoparasites generalist and played a role as accidental host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Publications reveal that the size of P. volitans in Veracruz is 248.1±48.2 mm and the weight is 279.2±221.8 gr [11]. Likewise, it presents endoparasites (trematodes, cestodes and nematodes) with a prevalence of less than 30% and heavy metals in the tissues (Cd=0.03, Pb=0.66, V=7.3 and Zn=0.43 mg kg-1 dry weight) whose concentrations do not exceed official standards [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Publications reveal that the size of P. volitans in Veracruz is 248.1±48.2 mm and the weight is 279.2±221.8 gr [11]. Likewise, it presents endoparasites (trematodes, cestodes and nematodes) with a prevalence of less than 30% and heavy metals in the tissues (Cd=0.03, Pb=0.66, V=7.3 and Zn=0.43 mg kg-1 dry weight) whose concentrations do not exceed official standards [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since P. volitans was first reported in the Veracruz Reef System National Park (VRSNP) in 2012 (Santander-Monsalvo et al 2012), local authorities have been reporting its presence in the park. Despite ongoing reports and with the exception of the study by Montoya-Mendoza et al (2017), who analyzed the parasites of P. volitans in this area, no studies on the biology of the species in this new environment have been published. Therefore, in order to produce novel information on P. volitans, the present study tested sampling at different depths and times on a silt flat south of the VRSNP with a fishing gear that allowed collecting representative samples of all sizes.…”
mentioning
confidence: 99%
“…It has to be noted that they even share parasites records (L. floridense, metacercarie of Didymozoidae, larva of Tetraphyllidea, and Pseudocapillaria sp. ), with the invasive scorpaenid Pterois volitans, the red lionfish, from the same locality (Montoya-Mendoza et al, 2017b). These observations showed that most adult parasites registered infest local scorpaenids, and that may be related to their distribution area, but now they can also be found in invasive scorpaenids, probably due to the transfaunal phenomenon displayed by larval forms.…”
Section: Discussionmentioning
confidence: 67%